Elections and Property Rights: A Natural Experiment From Russia. (March 2016) - Frye, Timothy; Yakovlev, Andrei
The relative bargaining power of rulers and right holders is thought to be a key determinant of property rights, but because it both shapes and is shaped by property rights, it is difficult to estimate the impact of bargaining power on property rights. We take advantage of a natural experiment by comparing the responses of managers interviewed just before and just after a surprising parliamentary election in Russia that weakened the relative bargaining power of the ruling party. This electoral shock had little impact on the perceived property rights of the average firm, but firms with close economic ties to the state viewed their property as more vulnerable after the election. By exploiting largely exogenous variation in the timing of survey interviews, we estimate the impact of bargaining power on property rights with greater precision. We also contribute to the literature on elections under autocracy by focusing on their economic, rather than political, impacts on individuals.